Effect of lignosulphonates on Vanilla planifolia shoot multiplication, regeneration and metabolism - Wan Abdullah, Wan Muhamad Asrul Nizam; Low, Lee Yoon; Mohd Ramli Alzaki, Siti Bahijah Mumaiyizah; Qian, Yee Chai; Loh, Jiun Yan; Abdullah, Janna Ong; Lai, Kok Song (Springer, 2020)
Vanilla planifolia (V. planifolia) is a valuable orchidaceous plant, commonly grown for its pods that are used to produce the flavouring vanilla extract. Here, we evaluated the effect of calcium lignosulphonate (Ca-LIGN) and sodium lignosulphonate (Na-LIGN) on multiplication and regeneration of V. planifolia shoot tip culture. In 150 mg L−1 Ca-LIGN medium, the most number of shoots per explant (5.78 ± 0.63) was successfully obtained. Besides, Ca-LIGN also enhanced the shoot bud and primordial formation rate, as seen under scanning electron microscopy. In contrast, medium containing 150 mg L−1 Na-LIGN recorded the highest average of shoot length (4.72 ± 0.30 cm). Meanwhile, the best growth of root length (1.8 ± 0.32 cm) and root induction (96.67 ± 5.16%) were recorded on the explants treated with 150 mg L−1 Na-LIGN rooting medium. All rooted plantlets successfully acclimatized in the greenhouse (100.00% survival rate). Further biochemical analysis revealed that Ca-LIGN increased the total protein, chlorophyll, sugar, flavonoid and phenolic contents of V. planifolia. Notably, expression of both ribulose-1,5-bisphosphate carboxylase (Rubisco) and phosphoenolpyruvate carboxylase (PEPC) genes were also elevated under the treatment of Ca-LIGN, implying a positive role in the photosynthetic process. Taken together, LIGN being an environmental friendly product could be used to enhance the growth and micropropagation of V. planifolia.